Odor profile of different varieties of extra-virgin olive oil during deep frying using an electronic nose and SPME-GC-FID - Messina, Valeria Marisa (2011)
The aim of the performed work was to evaluate with an electronic nose changes in odor profile of Arauco and Arbequina varieties of extra-virgin olive oil during deep-frying. Changes in odor were analyzed using an electronic nose composed of 16 sensors. Volatile compounds were analyzed by SPME-GC-FID. Principal Component Analysis was applied for electronic results. Arauco variety showed the highest response for sensors. Statistical analysis for volatile compounds indicated a significant (P<0.001) interaction between variety and time of frying processes. Arauco variety showed the highest production of volatile compounds at 60 min of deep frying. The two varieties presented distinct patterns of volatile products, being clearly identified with the electronic nose.